2019
DOI: 10.1177/1350650119851886
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of the effects of additional load phase and amplitude on fretting wear

Abstract: Fretting wear is a major form of fretting damage involving various factors, such as material properties, surface roughness, surface topography, lubrication conditions, environment temperature, type of loading, and loading phase difference. In this study, ABAQUS is used to establish three models to simulate the variation of wear depth with the amplitude of additional load. The influence of the phase difference between additional load and original load is considered. Four phase difference angles are involved, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…It is found that the fretting fatigue cracks perpendicular to the contact center often originate in the sub surface instead of the contact surface [13] . The Mises equivalent stress distribution along depth direction is extracted as shown in figure 6(a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the fretting fatigue cracks perpendicular to the contact center often originate in the sub surface instead of the contact surface [13] . The Mises equivalent stress distribution along depth direction is extracted as shown in figure 6(a).…”
Section: Resultsmentioning
confidence: 99%
“…The material response fretting map associated with fretting regimes map has been proposed which indicates that both fretting wear and fretting fatigue compete on the mixed regime [6] . Finite element (FE) models have been developed by many authors for fretting computations [7][8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%